Performance of variable-orifice nozzles for liquid fertilizer applications - Sharda, Ajay; Fulton, J. P.; Taylor, R. K. (My University, 2016)
Variable-rate application continues to gain interest among precision agriculture practitioners including the use of crop sensor technology for application of nitrogen in grain crops. For liquid fertilizers, variable-orifice nozzles are being implemented since they provide a much larger nozzle flow range compared to traditional fixed orifice nozzles. However, understanding the performance of variable-orifice nozzles under different field operating conditions has been limited. Therefore, the objective of this study was to evaluate the performance of variable orifice nozzles in support of variable-rate application. Two common variable-orifice nozzles offered by different companies were selected for this study. They were tested over three flow ranges (0.76 to 1.89 L/min) with all tests replicated three times. A commercially available 18.6-m, wet boom sprayer equipped with 37 nozzle bodies was used. Nozzles were numbered but then randomly assigned a position along the boom. To evaluate the performance of an individual nozzle, three random nozzle locations along the spray boom were established for both sets of nozzles. Therefore, 18 tests per replication were required to include the 3 flow rates, 3 different locations, and 2 nozzle types. Once the desired flow rate test was established, tip flow was measured using SpotOn Sprayer Calibrator technology. Tip flows were recorded and statistical analyses performed to evaluate flow uniformity (CV) across the boom but also detect off-rate errors by individual nozzles and locations across the boom. With the exception of a few nozzles, the uniformity across the spray boom, as defined by the CV, was acceptable for both nozzle types over approximately a 2:1 flow range. Both nozzle types were less uniform at the low flow rate. There were three nozzles of each type that resulted in unacceptable flow errors in multiple tests. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Sharda, A., Fulton, J. P., & Taylor, R. K. (2016). Performance of variable-orifice nozzles for liquid fertilizer applications. Applied Engineering in Agriculture, 32(3), 347-352. doi:10.13031/aea.32.11428
Keywords: Nozzles; Precision Agriculture; Sprayer; Uniformity; Variable Rate; Agriculture